Directions for the implementation of foreign experience in operative and investigative counteraction to intentional murders by criminal police units (on the example of Canada and the USA) - Ye. S. Khyzhnyak (Law and Safety)
Recently, scientific interest in the study of foreign experience in combating criminal illegality among domestic scientists is constantly growing, which indicates an effort to investigate the best preventive practices of separate countries and the search for ways of their implementation in Ukraine. However, with regard to the direct study of the foreign experience of operative and investigative countermeasures against intentional murders by police units of various foreign countries, there is a lack of such studies today, which increases the relevance of the chosen direction and gives prospects for determining effective practices using a targeted approach to combating deliberate murders and defining such a model of operative and investigative activity. The choice of an appropriate strategy by a particular state and the formation of an appropriate preventive program or a program to combat criminal wrongdoing is determined not only by the current criminogenic situation in this country and in the world in general, but also by the relevant historical, cultural and religious traditions. When considering the specifics of combating criminal wrongdoing in a particular country, it is necessary to take into account the country's membership of the corresponding criminological system. Modern criminology distinguishes Anglo-American, Western European, East Asian, socialist, Muslim and mixed criminological systems.